INCIDENTAL VOCABULARY LEARNING - Otamurodova Salomat (Journal Park Publishing, 2022)
This article reveals awesome examples of incidental learning of a child developing vocabulary. Students can acquire vocabulary incidentally by engaging in rich oral-language experiences at home and at school, listening to books read aloud to them, and reading widely on their own. Parents encourage their children by asking many questions and assist them to learn about things and ideas, when they come to school with oral vocabularies many times larger than children from disadvantaged homes.
Keywords: incidental; background; language drawbacks